Early organization, commercialization and weaponization of social media in the entertainment industry: A case study, Bones, season 6 (2010–2011) - James, Susan E. (Cogent social sciences, 2017)
As a television series, the Fox procedural crime drama Bones is exceptional. Having completed its twelfth and final season (2017), it is the longest running drama in the studio’s history. It is also a pioneer in its interactions with social media, offering a precedent-setting early example of online potential for organizing, commercializing and weaponizing social media platforms. During its sixth season (2010-2011) interactions between fans on social media and showrunners erupted into an internet war which when organized into an analytical model demonstrates the potential damage such conflict can cause not only to a specific television production but by extension to its showrunners as well. This transformative moment in the history of television illustrates the point at which fans who had once communicated individually now had means to connect as active online aggregates and express their views across multiple public forums. This case study illustrates the convergence of social and broadcast media and demonstrates an elemental shift in the interpersonal dynamic employed by viewers and showrunners. Considered in this article are the showrunners’ initial narrative intentions, how those intentions changed, and how they ran into conflict with the expectations of social media fans. Using this analysis and the resulting metrics of ratings, DVD sales and advertising costs, a construct can be formed that suggests the ways in which such a conflict can affect overall audience viewing patterns, impact future projects, and how social media, itself, has become a recognized and increasingly powerful entertainment tool.